Single axis solar tracker - Syed Omar, Syed Mohd Harussani (2010)
The Single Axis Solar Tracker is created to track the maximum sun. This project is invented especially to prevent wasting energy during sunrise to sunset. This project can increase the output voltage and produce maximum power daily using photovoltaic. Now days they are many trackers available in market but most of them cost a lot, wasting so much energy such as wasting energy on motor since the power require to rotate the photo-voltaic module is high and very complicated design. To completely specify the position of the sun it is necessary to specify three coordinates. However, if one assumes the distance from the sun to the Earth to be constant, the position of the sun can be specified using two coordinates. Two common choices are the solar altitude and the azimuth. The purpose of this project is to compare the power output produce by using tracker and fixed angle. This project use Programmable Interface Controller (PIC) for controlled the tracker. Photo-voltaic, or PV for short, is a technology in which light is converted into electrical power. One of the applications of PV is in solar tracker. A solar tracker is a equipment for operating a solar photovoltaic panel or concentrating solar reflector or lens forward sun-concentrates, especially in solar cell application, require high degree of accuracy to ensure that the concentrated sunlight is dedicated precisely to the power device. Solar tracker is invented because solar panel disables to move toward the sunlight when the sun moves from east to west. In order to produce maximum power output, solar tracker is design with motor so that the solar panel will move toward the position of sun. To control the solar panel so that it will always face the sun, the circuit has timer that consistent to the sun movement. The timer indicates the time to move solar panel in 12 hours. It moves the solar panel every one hour. It gives signal to the motor to move the solar panel. When the solar panel face directly to the sun and has maximum concentrated sunlight to the solar panel, the maximum power output will produce. The solar tracker is design as active tracker. It moves according to the sun movement and controlled by microcontroller.